A case of spinal muscular atrophy type 2 in a child: a genetic condition rarely detected in primary care / Siti Mariam Abu Hussain ... [et al.] - Abu Hussain, Siti Mariam; Shibraumalisi, Nur Amirah; Miptah, Hayatul Najaa; Ramli, Anis Safura (Faculty of Medicine, 2024)
Spinal muscular atrophy (SMA) is a neurodegenerative disease affecting 4 out of 10,000 live births. It is an autosomal recessive genetic condition caused by mutations of the survival motor neuron gene 1 (SMN1), located at chromosome 5q. There are five types of SMA, from Type 0 to Type 4. Depending on the types, SMA can cause severe disability and death. This case report presents a case of a six-month old baby boy with gross motor developmental regression. There was a missed opportunity to detect this case in primary care. The baby was referred by a private paediatrician to a government hospital's outpatient paediatric clinic for losing his ability to roll over, lift his buttocks, and sit without support. Genetic testing confirmed the diagnosis of SMA Type 2. Receiving the diagnosis and caring for a child with SMA is a lifechanging event for the parents and caregivers. The availability of gene therapy may change the prognosis and outcome of patients with SMA and should be offered if available. This case highlights the impact of the child's illness on the family and the importance of a multidisciplinary team approach in managing SMA. Primary care physicians play a key role in conducting thorough child health surveillance to ensure early identification and providing support to the child and the parents holistically as the disease progresses into adulthood. This includes providing long-term psychosocial support to improve their quality of life.